O nieistnieniu trzeciej kategorii podmiotowej w prawie prywatnym - Karkut, Daniel (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
The issue of the third category of entities has been presented in this study. Various ideas and conceptions were formulated in the Polish civil law doctrine — concerning the problem mentioned above. Not every author agreed that there were basics for a theory about the existence of the third category of entities. It was important to quote some of the rulings in the discussed scope. Furthermore, the study contains attempts to look at the problem from the other side and postulates to make some fundamental changes in regulations of the Polish Civil Code in the discussed area — the issue of limited legal entities operating in civil law for a long time such entities were recognized and regulated in Art. 331 of the Polish Civil Code. The aim of this article was to find a way to simplify the matter considered by presenting the idea to drop some crucial terms that are in constant use in such considerations.
Keywords: trzecia kategoria podmiotowa; podmioty; osoby prawne; osoba prawna; kodeks cywilny